The U.S. Indo-Pacific strategy and its implications for U.S.-ASEAN economic governance architecture - Pitakdumrongkit, Kaewkamol (2021)
During his visit to Asia in November 2017, President Donald Trump announced his vision of a “Free and Open Indo-Pacific” as the U.S. approach to the region. The Department of State unveiled in detail the economic elements of the Indo-Pacific strategy in April 2018. These economic policies were reiterated by Vice President Mike Pence at the Asia-Pacific Economic Cooperation (APEC) CEO Summit in Papua New Guinea in November 2018. For instance, Pence maintained that Washington plans to “make bilateral trade agreements with any Indo-Pacific nation that wants to be our partner and that will abide by the principles of fair and reciprocal trade,” promote private sector investment, and assist regional states on sustainable infrastructure development. On December 31, Trump signed into law the Asia Reassurance Initiative Act (ARIA) passed by the U.S. Congress earlier that month. ARIA further advances the strategy by mandating the executive branch to “develop a long-term strategic vision and a comprehensive, multifaceted, and principled United States policy for the Indo-Pacific region.” Moreover, the text authorizes $1.5 billion to “the Department of State, United States Agency for International Development [USAID], and, as appropriate, the Department of Defense . . . for each of the fiscal years 2019 through 2023, which shall be used” to achieve several objectives including ensuring “the regulatory environments for trade, infrastructure, and investment in partner countries are transparent, open, and free of corruption.” Against this backdrop, this chapter examines the effects of the U.S. Indo-Pacific strategy on the future of U.S.-ASEAN economic governance architecture. “Strategy” refers to “the collection of plans and policies that comprise the state’s deliberate effort to harness political, military, diplomatic, and economic tools together to advance that state’s national interest.” Such a study is warranted for a few reasons. First, the jury is still out on the degree to which this strategy would align or clash with different approaches and policies supported by Southeast Asian governments. Clashes of ideas and policies can result in not only failed implementation of the U.S. strategy but also competing economic initiatives which could undermine the future of U.S.-ASEAN trade and investment ties. Therefore, this research is aimed at: 1) assessing how the U.S. Indo-Pacific strategy would interact with Southeast Asian nations’ policies to shape the future development of regional economic architectures, and 2) forging policy recommendations for the U.S. and ASEAN governments on how they could jointly pursue regional economic institution-building. The questions I explore include: 1) What are the economic components of the U.S. Indo-Pacific strategy? 2) How will this strategy and Southeast Asian countries’ economic agendas/policies interact to shape the future advancement of regional economic architecture? and 3) What should American and ASEAN governments do to foster cooperation and lessen conflict among their different policies regarding economic regionalism? The chapter is organized as follows. The next part discusses the economic components of the Indo-Pacific strategy under the Trump administration. The second section examines the interactions between this strategy and the economic agendas of the Association of Southeast Asian Nations (ASEAN) to highlight the areas of complementarities and clashes. The last section provides policy recommendations for American and Southeast Asian governments to augment synergies and ameliorate clashes among their policies.